Differential adhesion of fibroblast and neuroblastoma cells on size- and geometry-controlled nanofibrils of the extracellular matrix - Kaiser, Peter; Spatz, Joachim P. (Soft matter, 2010)
We present a universal method to produce highly regular arrays of nanofibrils constituted by the extracellular matrix (ECM) proteins fibronectin (FN), collagen I (COL I) and EHS laminin (EHS LN). Adjusting the de-wetting parameters of a protein solution on a hydrophobic silicon micropillar structure, we control the mean nanofibril diameter between 20 nm and 160 nm. Array geometry predetermines nanofibril diameter, while protein concentration and de-wetting speed have to be adapted to yield high regularity. ECM nanofibrils span the space between adjacent pillars and immunofluorescence labelling of LN and FN nanofibrils allows us to discriminate both species in mixed networks. The biological function of ECM nanofibrils was verified in cell adhesion experiments after transfer of the nanofibrils onto non-adhesive polyethylene glycol (PEG) hydrogels. Co-cultures of fibroblasts and neuroblastoma cells on vertically arranged nanofibrils of FN and LN showed differential adhesion of the distinct cell types.
Online veröffentlicht am 12. Oktober 2009
Gesehen am 28.02.2023